APLIKASI DIDACTICAL DESIGN RESEARCH DALAM MENGANALISIS KESULITAN BELAJAR SISWA SMP MEMPELAJARI MATERI ALJABAR - Ardiansari, Lia (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2016)
The purpose of this study was to describe the learningobstacle of students in junior VII in algebra. Researchers gavetest questions to students, interviews and analyze documents.Then the students' answers were analyzed in depth anddisaggregated by didactical obstacle, epistemoligical obstacleand ontogonical obstacle. The cause of these learningobstacles can be seen from many things, among others due toinaccuracy in reading, inaccuracy in thinking, weakness in theanalysis of the problem, and lack of tenacious. Besides thelearning obstacle is thought to arise such as the design ofdidactic presented using the "quick way" so as not providingunderstanding of the concept for students, design didacticpresented in its final form that gives less opportunity forstudents to explore their understanding, contains a "jumpingthinking" large enough so that the less attention to cognitiveprocesses students will still have many difficulties in adjusting tothe thought of thinking arithmetic algebra (abstract), theconcepts presented are not systematic and do not support athorough understanding of the material to be learned.